Important role of volatile-char interactions in enhancing PM1 emission during the combustion of volatiles from biosolid - Chen, Xujun; Liaw, Sui Boon; Wu, Hongwei (Elsevier, 2017)
Abstract A three-stage pyrolysis/combustion reactor was used to demonstrate the importance of volatile–char interactions in inorganic particulate matter (PM) emission from the combustion of biosolid volatiles. It consists of a two-stage quartz reactor (including an inner drop-tube/fixed-bed pyrolyser as Stage I and an outer fixed-bed as Stage II) cascaded into a large drop-tube furnace (DTF, Stage III). The unique reactor design enables the volatiles that are produced in situ from the fast pyrolysis of cellulose, polyethylene or acid-washed biosolid in Stage I to pass through a preloaded bed of slow-pyrolysis biosolid char in Stage II then be immediately combusted (achieving complete combustion) in the DTF as Stage III at 1300 °C. Limited by quartz maximum working temperature (in Stages I and II), two temperatures (800 or 1000 °C) were considered for preparing the bed of char and generating the in situ volatiles. The results clearly show that volatile–char interactions lead to significant changes in the particle size distributions (PSDs) of PM emitted from the combustion of volatiles produced in situ from cellulose, polyethylene or acid-washed biosolid pyrolysis. The volatile–char interactions increase the yield of PM1 (i.e. PM with aerodynamic diameter <1 µm), dominantly PM0.1 (i.e. PM with aerodynamic diameter <0.1 µm). The results show that small non-oxygenated reactive species (especially H free radicals) in the fresh volatiles can react with the chars to enhance the release of alkalis (Na and K) as well as P and S in the chars. The released Na, K, P and S can react to form alkali metaphosphate and sulphate which subsequently form PM1 during volatiles combustion. It is also evident that volatile–char interactions convert some of Pb and Cr in the biosolid chars into volatile forms which are released and then contribute to PM1 emission.